Medicines prescription quality for geriatric patients - Oscanoa, Teodoro (2005)
Objective: To determine major polypharmacy (more than 4 drugs) medicines prescription quality among frail elderly inpatients. Materials and Methods: The setting was the Geriatric Department of Almenara Hospital, in Lima, Peru. Inappropriate prescribing was measured in 76 frail elderly inpatients applying the Medication Appropriateness Index (MAI). Results: The number of regularly scheduled medications was 456 (5,92±1,03 per patient); 69 (90,8%) patients had more than 1 medication with MAI criteria rated as inappropriate. The most common problems involved were unpractical directions (75%), duration (69,7%), effectiveness (52,6%), and cost (52,6%). The most common drug types with MAI problems included cardiovascular (61,8%), gastric (28,9%), central nervous system (27,6%) and musculoskeletal (17,1%). Multivariable analysis revealed that the number of prescriptions (p<0,001) and 3 of the quality of life indicators as measured by the Coop/Wonca (physical form p<0,001, pain p<0,05, and social support p <0,05) were related to higher MAI scores. The number of drugs per patient on admission decreased at discharge (5,92±1,03 and 3,4±1,40 respectively, p<0,05). Conclusions: Prescribing major polypharmacy inappropriate medications is frequent in frail elderly inpatients.